GREENHOUSE SYSTEM WITH FORCED AIR FLOW FOR PRE-DISTILLED KAFFIR (CITRUS HYSTRIX) LEAF TREATMENT - Cahyani , Chandrawati; Nurhadianty, Vivi; Sarosa, Aji Hendra; Muttaqin, Moch Fitron; Hidayat, Fahrul Huzain; Sarumpaet, Dicky Gabriel Partogi; Safitri , Mellyantika Alga; Miranti , Thiara Jatayuning; Rifdah, Naufaliyah Rifdah (Jurnal Rekayasa Mesin, 2024)
The greenhouse effect, which is a global issue, can provide benefits in the agricultural sector, especially in the processing of essential oils, which require drying raw materials before being purified. This is necessary to increase process efficiency, one of which is processing kaffir lime leaves. Drying is generally done in a simple way, but it has problems such as high-water content (approximately 15%), unstable weather, and slow drying speeds that cause leaf damage and fungus affecting essential oil quality. The solution is to utilize suitable technology, such as a greenhouse system. The study compares greenhouse drying methods with forced airflow and open sun drying, focusing on moisture content. The moisture content was measured using a moisture balance at each drying time. The result is that Greenhouse Force Circulation (GFC) drying effectively decreases kaffir lime leaves' moisture compared to Open Sun Drying (OSD), as evidenced by its higher drying rate.